92.7k views
0 votes
F(x) = 2x + 5

g() = 5x - 3
h(x) = 7
15. f(x) + g(x) =
16. f(x)- g(x) =
17. h(x) · g(x) =

Help w all pls

User Trotter
by
4.2k points

1 Answer

2 votes

9514 1404 393

Answer:

15. f(x) +g(x) = 7x +2

16. f(x) -g(x) = -3x +8

17. h(x) · g(x) = 35x -21

Explanation:

Substitute the function definition for each function expression and simplify.

__

15. f(x) + g(x) = (2x +5) +(5x -3)

f(x) +g(x) = 7x +2

__

16. f(x) - g(x) = (2x +5) -(5x -3)

f(x) -g(x) = -3x +8

__

17. h(x) · g(x) = (7) · (5x -3)

h(x) · g(x) = 35x -21

User Fadi Omar
by
4.8k points